The Role of Subjective and Objective Social Status in the Generation of Envy - Bolló, Henrietta; Háger, Dzsenifer Roxána; Galvan, Manuel; Orosz, Gábor (Frontiers in Psychology, 2020)
Envy is a negative emotion experienced in response to another person’s higher status. However, little is known about the decomposition of its most important element: status. The present research investigates the two main forms of social status (objective and subjective) in the generation of envy. In Study 1 participants recounted real-life situations when they felt envious and in Study 2 we examined whether the effect was the same in a controlled situation. We consistently found that those who were the most respected in the eyes of others were envied more than the richest ones. Furthermore, perceived deservingness of the superior other’s success differentiated between benign and malicious envy. Although previous studies focused on material comparisons when investigated envy, our results indicate that envy is rather a subjective social status related emotion. Not the material, but social advantage of the superior other causes the most painful envy and future studies should put more emphasis on this type of social comparisons in envy research.